Gravity at Sixty: The Workhorse Model of Trade - Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
On the eve of its 60th anniversary, the gravity model of trade is a 'celebrity', due to its intuitive appeal, solid theoretical foundations, and remarkable empirical success. Yet, many economists still view gravity simply as an intuitive but naive reduced-form estimating equation and apply it without guidance from theory, while others are skeptical about its usefulness for counterfactual projections. The objective of this paper is to offer a historical overview of its evolution from an a-theoretical application to an estimating computable general equilibrium (E-CGE) model, which can be nested in more complex frameworks. Along the way, I address some misconceptions about the gravity model, summarize the current best practices for gravity estimations, and highlight some properties that have made gravity so successful.
Keywords: F13; F14; F16; 330; structural gravity; evolution; theory; estimation general equilibrium